Urban wastewater and agricultural reuse challenges in India - Amerasinghe, Priyanie H.; Bhardwaj, R.M.; Scott, C.; Jella, Kiran; Marshall, F. (International Water Management Institute, 2013)
More than 1 million hectares of urban land in India could be irrigated for crops if wastewater was made safe for use. Lack of systematic data collection by municipalities makes it difficult to accurately assess the wastewater generation or estimate the total amount of urban area under wastewater irrigation, so the potential of urban and peri-urban farming could be even greater. This study attempted to analyze the current status of wastewater generation, its uses and livelihood benefits especially in agriculture, based on national data and case studies from Ahmedabad, New Delhi, Hyderabad, Kanpur and Kolkata.